1999
DOI: 10.1098/rspb.1999.0700
|View full text |Cite
|
Sign up to set email alerts
|

Moon and sun compasses in sandhoppers rely on two separate chronometric mechanisms

Abstract: The relationship between the chronometric system of compensation for the apparent movement of the sun and that for the moon has been the subject of several, never proven, hypotheses. Our studies on sandhoppers have demonstrated that the chronometric mechanism of the moon compass is separate from that of the sun compass. They show (i) that a period of seven days in constant darkness has no in£uence on the capacity for orientation, either solar or lunar, and indicates the presence of one or more continuously ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
2
18
1
Order By: Relevance
“…(1) Sandhoppers tested under natural conditions of sun during the day show correct identification of the orienting factor Pardi and Ercolini, 1986); the same is well known for moon orientation at night Papi and Pardi, 1959;Papi, 1960;Enright, 1961;Enright, 1972;Ugolini, 2003;Ugolini et al, 1999a;Ugolini et al, 1999b;Ugolini et al, 2003) (see also present results).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…(1) Sandhoppers tested under natural conditions of sun during the day show correct identification of the orienting factor Pardi and Ercolini, 1986); the same is well known for moon orientation at night Papi and Pardi, 1959;Papi, 1960;Enright, 1961;Enright, 1972;Ugolini, 2003;Ugolini et al, 1999a;Ugolini et al, 1999b;Ugolini et al, 2003) (see also present results).…”
Section: Discussionsupporting
confidence: 56%
“…It has long been known Pardi and Papi, 1953) that both the sun and the moon compasses are used by sandhoppers, like Talitrus saltator (Montagu), and the relationships between compass systems of orientation have been investigated (Ugolini et al, 1999b;Ugolini, 2003;Meschini et al, 2008). As pointed out previously (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that T. saltator is currently, to our knowledge, the only animal species in which an innate setting of the moon compass has been demonstrated. Indeed, T. saltator possesses two innate compass systems for astronomical orientation (the moon and the sun compass) and it has recently been demonstrated that their chronometric components are separate (Ugolini et al 1999b). Because the innate ecologically efficient direction indicated by the two compasses is the same, differences between the two orienting systems are due to the chronometric mechanisms: one for compensation for the apparent motion of the sun , the other for lunar compensation Papi 1960).…”
Section: Resultsmentioning
confidence: 99%
“…The moon compass coexists with a sun compass, but the two chronometric mechanisms are independent of each other (Ugolini et al 1999b). The use of the moon as an orienting factor, the existence of a moon compass and of separate chronometric mechanisms for sun and moon compensation, and the use of an artificial light source to reproduce good moon orientation have already been demonstrated in sandhoppers (Pardi & Papi 1952;Pardi & Ercolini 1986;Ugolini et al 1999aUgolini et al , 2002aUgolini et al , 2005).…”
mentioning
confidence: 99%